Tausug & the Sulu Sultanate - Asreemoro, 1977-; Abu Bakar Ahmad (Malaysia: Saba Islamic Media, 2008)
History of the Tausug people and their role in Islamic civilization in Sulu Sultanate.
Includes bibliographical references.
Keywords: Tausug (Philippine people); Sulu (Sultanate) -- History; Philippines -- Social life and customs